2017
DOI: 10.1002/2017jc013054
|View full text |Cite
|
Sign up to set email alerts
|

Role of Compressibility on Tsunami Propagation

Abstract: In the present paper, we aim to reduce the discrepancies between tsunami arrival times evaluated from tsunami models and real measurements considering the role of ocean compressibility. We perform qualitative studies to reveal the phase speed reduction rate via a modified version of the Mild Slope Equation for Weakly Compressible fluid (MSEWC) proposed by Sammarco et al. (2013). The model is validated against a 3‐D computational model. Physical properties of surface gravity waves are studied and compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…Actually, one can omit the gravity contribution in (2.1) for practical purposes. This conclusion was also confirmed by Abdolali & Kirby (2017), who showed the negligible role of g(∂ϕ/∂z) on hydroacoustic waves and surface gravity waves with short wavelength. Furthermore, we investigate different cases in a similar way, as shown in table 6.…”
Section: Resonant Wavessupporting
confidence: 67%
“…Actually, one can omit the gravity contribution in (2.1) for practical purposes. This conclusion was also confirmed by Abdolali & Kirby (2017), who showed the negligible role of g(∂ϕ/∂z) on hydroacoustic waves and surface gravity waves with short wavelength. Furthermore, we investigate different cases in a similar way, as shown in table 6.…”
Section: Resonant Wavessupporting
confidence: 67%
“…Note that (2.1) neglects the background compressibility of the static water column. This effect is important for the long range propagation of tsunamis, for example, but has been shown to be negligible for the acoustic modes of propagation; see Abdolali & Kirby (2017). The equation for pressure exerted by an elastic ice sheet on the underlying water column is given by Schulkes et al (1987),…”
Section: Governing Equationsmentioning
confidence: 99%
“…These assumptions are valid when the time periods are relatively short, and the corresponding phase speeds are low. It has been argued in various studies that the contributions of water compressibility and earth elasticity are vital not only for proper description of surface gravity waves 4–8 , but even more for waves travelling in the earth crust, such as P, S, Rayleigh and Love waves 9 , and acoustic-gravity waves that propagate in the water column 1016 , or couple with the sea-floor 17 . The latter travel at speeds that far exceed the maximum tsunami phase speed carrying information on the fault geometry and dynamics 15 , and thus could be employed for early tsunami warning systems 18 and inverse models 19 , if analysed real-time.…”
Section: Introductionmentioning
confidence: 99%
“…Tsunami waves have been extensively studied in recent years, with attention focused on various physical features including thermal or salinity-based density stratification 6,20 , compressibility of the water column 4,6,8,15,20–24 , elastic deformation of the underlying solid earth 17,20,25 or combined effect of compressibility, stratification, and elasticity 26 . These studies confirmed, independently, that the time lag between model output and observations is sensitive to many of the physical features virtually neglected.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation